A critical review of acoustic modeling and research on building façade. Issue 1 (March 2022) - Hu, Zhongyu; Zayed, Tarek; Cheng, Li
Noise pollution has been impacting negatively on living comfort and working environment for a long time. Acoustic treatment on building façade is one of the effective means to tackle this issue. Numerous articles were published over the past decades to address the acoustic related problems of building façade. However, a systematic review of the research development on façade acoustic technology is lacking. Therefore, this paper examines the published research articles from seven selected journals, in terms of the annual number of articles, citation counts, co-authorships, research locations, and keywords. The analyses show that interest in façade acoustics increased during the last two decades. Researchers from Europe and areas with a high density of tall buildings made significant contributions to this development. Based on keyword analysis, articles are categorized into three groups. These include sound insulation studies, studies on the effect of façade on street noise, and noise reduction techniques. The surveyed research topics comprise numerical modeling, experimental studies, ISO standard development, and analyses on annoyance level. Potential future directions are presented based on a summary of the limitations of the existing research. This paper offers researchers and engineers an in-depth understanding of the state-of-the-art of the current façade acoustic research. Additionally, potential future directions are identified based on the findings and limitations of the previous studies.